Freiheit als Kritik: Sozialphilosophie nach Foucault - Schubert, Karsten (transcript, 2018)
Freedom according to Foucault – the reconstruction and criticism of the debate about freedom as interpreted by Foucault has led to a new term of freedom: Freedom is the ability to cast a reflexive critical glance at one's own subjectification.